Naming the ideological reflexively: Contesting organizational norms and practices. (March 2014) - Dallyn, Sam
In this article I develop a reflexive conception of ideology that can be applied to the study of organizations. By drawing out and making explicit the researcher's role in naming a social phenomenon as ideological, I argue that a more consistent, reflexive and critically attuned notion of the ideological can be developed. The neglect of the position of the researcher in critical conceptions of ideology stems largely from a problematic division in existing approaches between the researcher, as objective expert, and researched. As an alternative, I build on the idea of research reflexivity in organization studies to develop a notion of ideology in which the partial position of the researcher is rendered explicit. To illustrate this conception of naming the ideological, I characterize the norms and practices of Job Centres as reflecting an ideology of capitalist welfare regulation. The article presents a fresh way of conceptualizing ideology as a reflexive analytical concept which can fruitfully be brought to bear on different aspects of organizations.